2008
DOI: 10.1007/s00125-008-1106-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and social deprivation independently influence metabolic control in children with type 1 diabetes

Abstract: Aims/hypothesis This study was performed to evaluate the influence of ethnicity and socioeconomic status (SES) on metabolic control in a population-based cohort of children with type 1 diabetes mellitus, and to evaluate whether any relationship between ethnicity and HbA 1c is mediated by SES. Methods We performed a retrospective review of all patients under age 16 years with type 1 diabetes (n=555) from 1995 to 2005 in the greater Auckland region, New Zealand. Diabetes care variables and HbA 1c values were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
95
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(110 citation statements)
references
References 36 publications
15
95
0
Order By: Relevance
“…These findings accord with other observations in diabetes in both paediatric and adult populations in other parts of the world [5][6][7]13] and within similar paediatric populations in the UK [8]. Access to more intensive insulin regimens (multiple daily injections) appeared better in the African population, but uptake of insulin pump therapy was less than other groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings accord with other observations in diabetes in both paediatric and adult populations in other parts of the world [5][6][7]13] and within similar paediatric populations in the UK [8]. Access to more intensive insulin regimens (multiple daily injections) appeared better in the African population, but uptake of insulin pump therapy was less than other groups.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age was 10.6 years (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], with an average duration of diabetes of 4.5 years. At each quarterly clinic visit, HbA 1c was measured, using the Siemens DCA1000 (Bayer) near-patient testing system (Siemens Healthcare Diagnostics Inc., Deerfield, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The focus on the natural course of microalbuminuria, the large number of children in the survey in a real-world setting, and the very homogeneous cohort of children regarding age and diabetes duration are major strengths of the present survey. To date, little is known about the development of diabetic complications and comorbidities in type 1 diabetes in different population groups (21,22,23,24). Differences in health status in immigrant and non-immigrant families may explain Figure 1 The rates (% and absolute numbers) of the 683 children with type 1 diabetes with normoalbuminuria, intermittent and persistent microalbuminuria at baseline, and the progression and regression of microalbuminuria after a follow-up of 5 years are depicted.…”
Section: Discussionmentioning
confidence: 99%
“…Principally, there is growing awareness of differences in health status between various population groups (24,25,26,27,28,29,30). The German Health Interview and Examination Survey for Children and Adolescents (KiGGS) conducted from 2003 to 2006 showed that general state of health is estimated to be lower in children with immigrant status compared with those with non-immigrant status (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation